CASE STUDY OF A PATIENT WITH HIV-AIDS AND VISCERAL LEISHMANIASIS CO-INFECTION IN MULTIPLE EPISODES - Silva, Elis Dionisio da; Andrade, Luiz Dias de; Araujo, Paulo Sergio Ramos de; Silveira, Vera Magalhaes; Padilha, Carlos Eduardo; Silva, Maria Almerice Lopes da; Medeiros, Zulma Maria de (Revista do Instituto de Medicina Tropical de São Paulo, 2013)
SUMMARY Report of a 45-year-old male farmer, a resident in the forest zone of Pernambuco, who was diagnosed with human immunodeficiency virus (HIV) in 1999 and treated using antiretroviral (ARV) drugs. In 2005, the first episode of visceral leishmaniasis (VL), as assessed by parasitological diagnosis of bone marrow aspirate, was recorded. When admitted to the hospital, the patient presented fever, hepatosplenomegaly, weight loss, and diarrhea. Since then, six additional episodes of VL occurred, with a frequency rate of one per year (2005-2012, except in 2008). In 2011, the patient presented a disseminated skin lesion caused by the amastigotes of Leishmania, as identified by histopathological assessment of skin biopsy samples. In 2005, he was treated with N-methyl-glucamine-antimony and amphotericin B deoxycholate. However, since 2006 because of a reported toxicity, the drug of choice was liposomal amphotericin B. As recommended by the Ministry of Health, this report emphasizes the need for HIV patients living in VL endemic areas to include this parasitosis in their follow-up protocol, particularly after the first infection of VL.